AKTIVITAS ANTIBAKTERI EKSTRAK BIJI KAPULAGA (Amomum compactum Sol. Ex Maton) - Dede Sukandar; Sandra Hermanto; Eka Rizki Amelia; Muhamad Zaenudin (Jurnal Kimia Terapan Indonesia, 2015)
Testing of antibacterial activity against ethyl acetate extract local cardamom seeds (Amomum compactum Sol. Ex Maton) has been performed. Extraction was carried out using the soxhlet method with methanol solvent and liquid-liquid partitioned with n-hexane, ethyl acetate and n-butanol solvent, antibacterial activity test was performed using the disc diffusion method, fractionation using column chromatography and characterization of active fractions using chromatography GCMS, UV-vis and FTIR spectroscopy. The test results showed that the antibacterial activity of ethyl acetate extract had the highest antibacterial activity against S. aureus and E. coli with inhibition zone diameter of respectively 15.15 ± 1.34 and 13.50 ± 0.70 mm at a concentration of 3200 mg/mL. Results of fractionation of the ethyl acetate fraction using column chromatography with a mobile phase of ethyl acetate: n-hexane (3: 2) yielded three fractions, namely F1 (14.6 mg), F2 (8.1 mg) and F3 (4.6 mg). Fraction 2 had the highest antibacterial activity against S. aureus with inhibition zone diameter of 12.34 ± 0.07 mm at a concentration of 800 ug/mL. The results of the characterization of the fraction 2 obtained using GCMS analysis of three antibacterial compounds suspected of 2.9-dihydroxy-1,8-cineol; 2,4-dihydroxy-1,8-cineol and 2,2-methylene bis [6- (1,1-dimethylethyl) -4-ethyl] phenol. The results of the F2 fraction characterization using UV-Vis spectroscopy showed the presence of group C = C conjugated chromophore at λmax 223 nm and are based on analysis using FTIR there -OH alcohol functional group (3372 cm-1), aliphatic -CH (2926 and 2854 cm-1) , C = C (1695 cm-1), aliphatic CH2 (1402 cm-1), CH3 aliphatic (1384 cm-1), and C-O (1203; 1126; 1091 and 1043 cm-1). Keywords: Antibacterial, S. aureus, E. coli, Amomum compactum Sol. Ex Maton, disk diffusion